AN INVESTIGATION INTO THE EFFECTS OF ORGANIC FERTILISER APPLICATION ON THE CHEMICAL COMPOSITION AND BIOLOGICAL ACTIVITY OF MEDICINAL PLANTS - Prinsloo, G.; Motsei, M.; Viljoen, J.; Mofokeng, M.; Phala, L. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The use of medicinal plants has increased significantly due to their known biological activity against common human, animal and plant pathogens. The increased use of these plants has led to some of these plants facing extinction in the wild due to a lack of cultivation to maintain sustainable populations. When plants are removed from their natural environment, changes in their chemical composition can be observed. Changes may occur due to environmental and geographical changes that the plants are exposed to. Cultivation of these plants under irrigation with the application of fertilisers also changes the chemical composition of their active compounds. A selection of important medicinal plants were subjected to organic fertiliser treatments, which included bone meal, gypsum, and an organic nitrogen source that was applied separately and in different combinations to obtain seven treatments. The fertiliser trials were harvested for two years. For all the treatments, ethanolic water and petroleum ether extracts were prepared. Successive fractions of ethyl acetate and methanol for the petroleum ether extracts were also prepared. All these extracts were evaluated for chemical differences by TLC and HPLC analysis. Many differences were observed, but it was not clear if the changes affected the biological activity of the plants. Bioassays using three different human bacteria were performed to test the activity of the extracts. Distinct differences in the biological activity were observed with extracts from the different organic fertiliser treatments.